The Use of Multiplication Cards in Improving Students’ Math Multiplication Learning Outcomes - Monasritha Amalia; Djatmiko Hidajat (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
Media innovation in math learning is essential to improving student understanding. This study aims to assess the improvement in students' math learning outcomes using multiplication card media. This research follows a classroom action research design consisting of three cycles. The research subjects were 13 fifth-grade students from SD Negeri Wironanggan 02. Three types of questions were used to measure student learning outcomes. The results indicated an improvement in student learning outcomes. In Cycle I, the average learning outcome was 58.462, increasing to 76.538 in Cycle II and 93.077 in Cycle III. The gain score between Cycle I and Cycle II was 0.435 (43.5%), which further increased to 0.705 (70.5%) between Cycle II and Cycle III. Based on these results, it can be concluded that the use of multiplication card media in learning enhances the learning outcomes of fifth-grade students at SD Negeri Wironanggan 02.